Assessing the frequency and magnitude of match impacts accrued during an elite rugby union playing season - Grainger, A.; McMahon, J. J.; Comfort, P. (International Journal of Performance Analysis in Sport, 2018)
The aim of this study was to identify position-related differences in absolute and relative match impacts in rugby union. Thirty-eight subjects were tracked, using GPS units containing inertial sensors, across one full playing season (n = 462 data sets). No difference in the number of impacts >9.01 G were observed between forwards (229 ± 160) and backs (226 ± 151). Forwards, however, experienced a greater absolute (p = 0.03) and relative (p = 0.003) number of impacts >13 G compared to backs. Full backs experienced the highest frequency of absolute impacts >9.01 G, which was significantly greater compared to locks (p = 0.001, d = 1.84), back row (p = 0.003, d = 0.68), out half (p = 0.036, d = 1.24) and wingers (p = 0.036, d = 0.76). Hookers experienced the highest relative frequency of impacts >9.01 G, which was significantly greater than locks (p < 0.001, d = 2.06), back row (p = 0.001, d = 1.10), outside halves (p = 0.001, d = 1.44) and wingers (p < 0.001, d = 1.19). Coaches should consider these findings when planning training sessions, as the frequency and magnitude of impacts experienced by positional groups vary during match play.